Czechosłowacka polityka bezpieczeństwa w latach 1918-1919 - Nowinowski, Sławomir M. (Acta Universitatis Lodziensis. Folia Historica, 1999)
The studies over the conception of security of Czechoslovakia was initiated during the First World War by Tomas Masaryk. They were recapitulated in the book The New Europe which was published in autumn 1918. According to the author, the close co-operation of Czechoslovakia, Yugoslavia and Poland, leading to the federation open for the rest of the states of that region should be the base of the political and economic stabilisation o f Central Europe. However that project was a kind of constructive solution of the problem, it abstracted from the political, economic and ethnic reality which minimised the chances of its realisation. In that period the activity of Eduard Beneś was concentrated on the attempts to get the strategic allied among the powers of Entent, who would be able to give Czechoslovakia the real guaranty of security. That role was taken up eventually by France, who declared her readiness for supporting the Czechoslovak territorial claims. The French military mission that had been sent to Prague took the control over the army of ČSR. During the period of preparation to the Paris Peace Conference the government of Czechoslovakia did not show the great interest in the conception of the League of Nations. It attempted to reach the security of the state by assuring the strategic frontiers for it. It is worth stressing that in general it ignored the national point of problem in spite of the fact that whole territory along the demanded frontiers with Austria, Germany and Hungary was inhabited by the people of those three nations whose attitude towards the Czechoslovak statehood was negative. On the Paris Peace Conference the Czechoslovak diplomacy did not manage to obtain the powers approbation of her conception of security. Eventually they accepted „the historical frontiers”, nevertheless that was considered as a great success of the I Republic. Signing the peace treaties with Austria and Germany (among the other these treaties limited the possibility of Anschluss and the number of military forces of these both states and forbade them the possessing of some category of arms) Czechoslovakia obtained the new guaranty of security. As the primeval member of the League of Nations it also obtained the guaranty assured by the Pact. Still a state of the international relations in Central-East Europe was far from that one that was wanted from the Prague’s point of view. The military circles of ČSR recognising the danger of the isolation of the state, appealed to the government for intensification of the military cooperation with France and for find the allies in the neighbourhood.